PENGARUH KEEFEKTIFAN DEWAN KOMISARIS INDEPENDEN TERHADAP MANAJEMEN LABA - Farida, Dessy Noor (PRESTASI, 2013)
Abstract Earnings information is information that is frequently used by the users of the financial statements to make decisions in accordance with their respective interests . Therefore , it takes good governance in order to ensure that the financial statements are free from elements of engineering . The purpose of this study was to prove the effectiveness effect commissioners and managerial ownership to earnings management . Manufacturing firms listed in Indonesian Stock Exchange 2008-20010 is the object of this study. Based on purposive sampling technique, it gets 48 firms. Multiple regression analysis using SPSS program. The result of the hypothesis test indicates that independent board of commissioners have significantly positive effect on discretionary accruals. This study also found size board and managerial ownership have not significantly on discretionary accruals. This reserachh have adjusted R square only 15,2 % Keywords: Discretionary Accruals, independent board of commisioners, size board,managerial ownership